2017
DOI: 10.1159/000481971
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting ROS-TFEB-Dependent Autophagy Enhances Salidroside-Induced Apoptosis in Human Chondrosarcoma Cells

Abstract: Background/Aims: Autophagy modulation has been considered a potential therapeutic strategy for human chondrosarcoma, and a previous study indicated that salidroside exhibits significant anti-carcinogenic activity. However, the ability of salidroside to induce autophagy and its role in human chondrosarcoma cell death remains unclear. Methods: We exposed SW1353 cells to different concentrations of salidroside (0.5, 1 and 2 mM) for 24 h. RT-PCR, Western-blotting, Immunocytofluorescence, and Luciferase Reporter As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 50 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…78 TFEB nuclear translocation upregulates autophagy-related regulators, including ATP6V0D1 , LAMP1 , CTSB , MAP1LC3B , and UVRAG. 79 Of note, emerging studies have demonstrated that TFEB serves as a bridge to mediate upstream regulators and autophagy progression in cancer cells. STUB1 regulates autophagy and mitochondrial biogenesis by modulating TFEB activity.…”
Section: Epigenetic Transcriptional and Post-transcriptional Regulamentioning
confidence: 99%
“…78 TFEB nuclear translocation upregulates autophagy-related regulators, including ATP6V0D1 , LAMP1 , CTSB , MAP1LC3B , and UVRAG. 79 Of note, emerging studies have demonstrated that TFEB serves as a bridge to mediate upstream regulators and autophagy progression in cancer cells. STUB1 regulates autophagy and mitochondrial biogenesis by modulating TFEB activity.…”
Section: Epigenetic Transcriptional and Post-transcriptional Regulamentioning
confidence: 99%
“…However, the mechanism that underlies the ivermectin‐mediated enhancement of TFE3 activity and nuclear translocation remains elusive. Recent studies have linked the accumulation of ROS to TFEB activation in the invasion and migration of cancer . TFE3 and TFEB share a similar structure that includes three critically important regions, and these two factors bind overlapping sets of promoters and are post‐transcriptionally regulated through a similar mechanism .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the free radical scavenging activity was observed in the present study. Therefore, it was speculated that some components, including verbascoside, iso-verbascoside and salidroside in a high dose of CTPG-W might immediately induce ROS generation to cause apoptosis of Eca-109 cells (41,42), and then ROS was scavenged by echinacoside. Another possible reason for the differences in ROS production by CTPG and CTPG-W is that different cell lines were used in this study and previous study (24).…”
Section: Discussionmentioning
confidence: 99%